Evaluation of wind power potential in shelek corridor (Kazakhstan) using weibull distribution function - Baizhuma, Zh.; Bolegenova, S. A.; Manatbayev, R. K.; Baktybekov, K.; Syzdykov, A. (International Journal of Mathematics and Physics, 2018)
Kazakhstan currently has one of the highest, per capita, carbon footprints in the world. There are heavy reliance (approx 85%) on coal for electricity production in Kazakhstan. Coal is a very carbon intensive fuel. A drive to moderate coal’s contribution to electricity production provides a driver for wind energy development. Finding a suitable location requires a detailed and often costly analysis of local wind conditions. Wind resource assessment is a crucial first step in gauging the potential of a site to produce energy from wind turbines. In this paper, the wind energy potential of Shelek corridor, located in the Almaty region in Kazakhstan were examined. Local wind speed distributions are represented by Weibull statistics. The results show that the average annual mean wind speed variation for Shelek corridor ranges from 4.0 to 8.0 m/s. The wind power density variation based on the Weibull analysis ranges from 280.0 to 320.0 W/m2. <div id="SL_button" class="SL_ImTranslatorLogo" style="background: rgba(0, 0, 0, 0) url(’moz-extension://a11bc875-1804-4fd7-8e5e-a70b44ba6b3c/content/img/util/imtranslator-s.png’) repeat scroll 0% 0%; display: none; opacity: 1;"> <input id="SL_locer" title="Зафиксировать язык" type="checkbox"> <select id="SL_lng_from" style="background: #ffffff url(’moz-extension://a11bc875-1804-4fd7-8e5e-a70b44ba6b3c/content/img/util/select.png’) no-repeat scroll 100% 0px;"> <option value="">undefined</option> </select> <select id="SL_lng_to" style="background: #ffffff url(’moz-extension://a11bc875-1804-4fd7-8e5e-a70b44ba6b3c/content/img/util/select.png’) no-repeat scroll 100% 0px;"> <option value="">undefined</option> </select> Звуковая функция ограничена 200 символами <input id="SL_BBL_locer" title="Показывать кнопку ImTranslator Bubble 3 секунд" checked="checked" type="checkbox"> Настройки : История : Обратная связь : Donate Закрыть